Relevansi Hadits Tentang Pendidikan Karakter dalam Menghadapi Era Disrupsi Teknologi: Studi Tematik Hadits Tentang Akhlak - Leni Maulida; Serlyana Yuriska (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The era of technological disruption brings major changes in life, including education and character building. Technological progress demands a balance between intellectual intelligence and moral values. In Islam, character education has a strong foundation, particularly in the hadiths of the Prophet Muhammad SAW. This study explores the relevance of hadiths on character education in facing digital era challenges using the prophetic ethics theory, which emphasizes transcendence, humanization, and liberation. Employing a library research method with a thematic (maudhu’i) approach, the research analyzes hadiths related to morals by categorizing and interpreting their moral messages. The study also connects these teachings with modern digital issues such as the ethical use of technology and online responsibility. Findings show that moral values in hadiths such as honesty, trustworthiness, discipline, and wisdom are essential in shaping individuals with integrity. Thus, integrating moral values into education is vital for preparing strong-charactered generations in the digital age.